Fallout : nuclear disasters in our world - Greeley, August (New York : PowerKids Press, 2003)
Explains the dangers nuclear disasters pose to the world and chronicle the events surrounding the nuclear disaster at Chernobyl and the affects it had on the world.
Nuclear energy -- The Chernobyl disaster -- The big cleanup -- Effects of Chernobyl -- Safe nuclear power.
Includes bibliographical references (p. 23) and index.
4.7.
4.7
3-6
Keywords: Nuclear accidents -- Juvenile literature; Nuclear accidents; Nuclear accidents